Motoric Cognitive Risk Syndrome: Could It Be Defined Through Increased Five-Times-Sit-to-Stand Test Time, Rather Than Slow Walking Speed? - Sekhon, Harmehr; Launay, Cyrille P.; Chabot, Julia; Allali, Gilles; Beauchet, Olivier (Frontiers in Aging Neuroscience, 2019)
Background. Slow walking speed, time to perform the Five-Times-Sit-to-Stand (FTSS) test and Motoric Cognitive Risk syndrome (MCR), which associates slow gait speed and subjective cognitive complaint, have separately been used to screen older individuals at risk of cognitive decline. The study aims to 1) compare the characteristics of older individuals with MCR defined with slow walking speed and/or increased FTSS time, and 2) examine the association of MCR and its motor components with amnestic Mild Cognitive Impairment (a-MCI) and non-amnestic MCI (na-MCI). Methods. A total of 633 individuals free of dementia were selected from the "Gait and Alzheimer Interactions Tracking" study, which is a cross-sectional study. Slow gait speed and increased FTSS time were used as criterion for the definition of MCR. Participants were separated in five groups based on MCR status: MCR defined with (1) slow gait speed exclusively (MCRs), (2) increased FTSS time exclusively (MCRf), (3) slow gait speed and increased FTSS time (MCRsaf), (4) MCR irrespective of the mobility test used (MCRsof) and (5) absence of MCR. Cognitive status (i.e., a-MCI, na-MCI, cognitively healthy) was also determined. Results. The prevalence of MCRs was higher compared to the prevalence of MCRf (12.0% versus 6.2% with P≤0.001). There was a small overlap (2.4%) between individuals with MCRs and MCRf, and an important overlap between individuals with MCRs and na-MCI (up to 50%). a-MCI and na-MCI were negatively (odd ratios (OR) ≤0.17 with P≤0.019) and positively (OR≥2.41 with P≤0.019) associated with MCRs, respectively. Conclusion. Individuals with MCRf are different than those with MCRs. MCRf status is not associated with MCI status compared to MCRs. MCRs was negatively associated with a-MCI and positively association with na-MCI.